2016
DOI: 10.1016/j.joen.2016.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting Periapical Inflammatory Condition Exacerbates Tooth Extraction–induced Bisphosphonate-related Osteonecrosis of the Jaw Lesions in Mice

Abstract: Introduction Surgical interventions such as tooth extraction increase a chance of developing osteonecrosis of the jaw (ONJ) in patients receiving bisphosphonates (BPs) for treatment of bone-related diseases. Tooth extraction is often performed to eliminate pre-existing pathological inflammatory conditions that make the tooth unsalvageable; however, the role of such conditions on bisphosphonate-related ONJ (BRONJ) development following tooth extraction is not clearly defined. Here, we examined the effects of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 23 publications
3
51
0
1
Order By: Relevance
“…However, in the present study few empty lacunae were observed in group III treated by Risedronate. This agrees with Song et al 2016 (36), who reported the presence of empty lacunae and necrotic bone in mice treated by bisphosphonates following tooth extraction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in the present study few empty lacunae were observed in group III treated by Risedronate. This agrees with Song et al 2016 (36), who reported the presence of empty lacunae and necrotic bone in mice treated by bisphosphonates following tooth extraction.…”
Section: Discussionsupporting
confidence: 92%
“…Bisphosphonates are thought to work by inhibition of osteoclastic activity. Other proposed mechanisms include alteration of bone turnover and inhibition of angiogenesis (36). Several studies have also suggested that bisphosphonates have a stimulatory effect on osteoblast proliferation and differentiation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Delaying the start of risk factor medications until surgical sites have healed, and ensuring appropriate perioperative management, including antibiotic coverage, are often effective means to prevent MRONJ associated with dentoalveolar surgery (Dimopoulos et al, ; Hoefert & Eufinger, ; Montefusco et al, ; Ripamonti et al, ; Vandone et al, ). However, periodontitis (PD) and periapical infection (Aghaloo et al, ; Aguirre, Akhter, Kimmel, Pingel, Williams et al, ; Li et al, ; Song et al, ) have also been identified as important risk factors for BRONJ/MRONJ in patients without recent dentoalveolar surgery (Carlson & Schlott, ; Eleutherakis‐Papaiakovou & Bamias, ; Khan et al, ; Marx, ; Voss et al, ). While oral diseases involving the periodontal tissues appear to contribute to MRONJ directly, they may also contribute to cases related to dentoalveolar surgery, since teeth that require extraction often have some degree of acute or chronic infection (e.g., infection from caries, periodontal disease).…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the small size of the animal requires reduced amount of the drug, rapid cumulative effects due to rapid mice metabolism, and the possibility of using genetically-manipulated animals to determine a cause-and-effect relationship between the target disruption of a gene and its function [21][22][23]. Several MRONJ models have been developed using mainly C57BL/6 and other mice strains (S1 Table), [15,17,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The C57BL/6 is the most widely used inbred strain and with a large source of genetically modified lines [40].…”
Section: Introductionmentioning
confidence: 99%